3113 – FORTY-EIGHT WEEK EFFICACY AND SAFETY OF PEGCETACOPLAN IN ADULT PATIENTS WITH PAROXYSMAL NOCTURNAL HEMOGLOBINURIA AND SUBOPTIMAL RESPONSE TO PRIOR ECULIZUMAB TREATMENT - de Latour, Régis Peffault; Szer, Jeffrey; Weitz, Ilene; Röth, Alexander; Höchsmann, Britta; Panse, Jens; Usuki, Kensuke; Griffin, Morag; Kiladjian, Jean-Jacques; de Castro, Carlos; Nishimori, Hisakazu; Tan, Lisa; et al. (Experimental hematology, 2021)
Pegcetacoplan (PEG) is a C3 complement inhibitor for the treatment of paroxysmal nocturnal hemoglobinuria (PNH). PEG was superior to eculizumab (ECU; C5-inhibitor) in improving hemoglobin (Hb) levels and clinical outcomes at Week 16 (phase 3 PEGASUS trial NCT03500549). Here, we report efficacy and safety of PEG through Week 48. Eighty PNH patients ≥18 years with Hb levels <10.5 g/dL despite stable ECU treatment (≥3 months) were enrolled. Patients completed a 4-week run-in with both ECU and PEG before 1:1 randomization to PEG (n=41) or ECU monotherapy (n=39). The primary endpoint was the change from baseline (CFB) in Hb to Week 16. Key secondary endpoints included adverse events (AEs). After the randomized control period (RCP), patients could continue to an open-label period (OLP), with a 4-week run-in for ECU patients (ECU-to-PEG), followed by PEG monotherapy for all patients through Week 48. Improved Hb levels observed at Week 16 were sustained during the OLP in PEG monotherapy patients. ECU-to-PEG patients experienced Hb improvement with mean Hb levels of 11.6 g/dL at Week 48 (CFB: 2.9 g/dL), while PEG-to-PEG patients maintained high Hb levels through the OLP with a mean Hb level of 11.3 g/dL at Week 48 (CFB: 2.6 g/dL). Serious AEs were reported by 30% of patients with 6% possibly related to PEG. Common AEs for PEG patients were injection site reactions (36%), hemolysis (24%), and diarrhea (21%). Overall, 12 patients (15%) discontinued PEG: 3 in RCP, 8 in OLP due to treatment-emergent AEs (6 in ECU-to-PEG, 2 in PEG-to-PEG), and one during follow-up; one patient withdrew due to physician decision. PEG-treated PNH patients experienced durable treatment effects in all efficacy parameters at Week 48 and the safety profile of PEG was consistent with previously reported data. The results suggest that PEG represents a new effective therapeutic option for PNH patients.